The Teaching Qualitification, Characteristics, Competence and Lecturer Performance : A Case Study at the University of Ilorin, Nigeria - Lucky, Esuh Ossai-Igwe (2013)
Generally, teachers are considered the most important element in the education system. Even though the issue of teachers' performance in relation to the teaching qualification, characteristics and competence has remained a contested issue in Nigeria, there is still a wide gap between the demand and supply of qualified teachers in Nigeria. This has however created opportunity for the increase in the influx of unqualified lecturers in Nigeria tertiary institutions particularly in the universities. This suggests that many lecturers have no required teaching qualifications, characteristics and competence that would assist them to perform their tasks effectively. Due to this, a cross-sectional study of questionnaire survey research design was conducted in this respect. Questionnaire data on teaching qualification, characteristics and competence were generated from 131 lecturers comprising of those with teaching qualification and those without teaching qualification in University of Illorin located Kwara State of Nigeria. The questionnaires were distributed through email and, drop-off and pick procedures. Overall, the findings from the testing of the hypotheses indicate that there is a significant relationship between teaching qualifications, lecturers' characteristics and lecturers' competence with lecturers' performance. From the t-test result, the study failed to find a significant difference between those teaching qualification and those with teaching qualification. The result further shows that lecturers' characteristic is the most important factor in predicting lecturers' performance. Based on this fact, it was concluded that both lecturers' characteristics and competence are the most important factors that predict lecturers' performance. Thus, the study recommends that lecturers and policy makers, which includes university authority, to give more consideration to lecturers competence and characteristics to enhance their performance. Finally, both the theoretical and practical implications are duly presented as well as that of the limitations of the study and suggestions for future study are included in this regard.